Political party financing and election reformations in Nigeria's 2015 general election: issues and impacts - Sule, Babayo (2018)
Periodic election is one of the major tenets of democratic rule and it is considered as a huge financial venture involving government spending for sponsoring electoral management body, political parties and contestants. Elections in Nigeria are often volatile with widespread irregularities that made them faulty and unacceptable. Political party financing and electoral process during the Nigeria's Fourth Republic became corrupted due to the influence of money politics. Hence, this study examined the process of political party financing and electoral reformation and its impacts on the outcome of the 2015 General Election. One of the major problems relating to the country’s election is how the regulations on political party financing was violated with illegal spending and corrupt practices which subsequently affected the election outcome and its credibility. This research used qualitative method whereby the data were obtained from informants who were selected from organisations and agencies relating to election, as well as anti-graft agencies, academicians and focus group. The data obtained from the field was analysed and discussed using content analysis and thematic interpretations. The findings of this research show that there was a clear violation of regulations on political party financing and massive corrupt practices amounting to trillions of Naira, particularly by the two major contending parties: APC and PDP. This money was sourced from government's treasury and illegally spent in bribing the stakeholders who were involved in the elections but, the election reformation helped immensely in producing an improved election in comparison with the previous ones. This research recommends that regulations on political party financing should be revisited and any future election should be conducted using electronic voting. In addition, financial activities of parties and candidates should be strictly monitored and violation of electoral laws by any party or candidate should be sanctioned severely.